Hepatic abscess by xanthogranulomatous cholecystitis and vesicular adenomyomatosis: a case report. - Vera-Portilla, Angel F. (2021)
Xanthogranulomatous cholecystitis (CXG) and Adenomyomatosis (VA) are rare, with few reports in our setting. The preoperative and intraoperative differentiation is difficult because it presents radiological and macroscopic characteristics, similar to cancer. It often presents as acute cholecystitis. And the diagnosis is established by the presence of fibrosis, foamy histiocytes, and Rokitansky-Aschoff sinuses, respectively. We present the case of a woman who came in for abdominal pain, nausea and vomiting. The tomography revealed a subcapsular liver collection. Surgery was performed and a hepatic abscess blocked by the omentum was evidenced, with multiple adhesions; and thickened-walled vesicle perforated in bacinete. Patient receives antibiotic therapy, progresses well, and histopathology concludes CXG and VA. CXG and VA are rare diseases associated with cholelithiasis. In our case, its association, and its complication with liver abscess, make it particularly exceptional. Requiring both surgery and histopathology to confirm them.